VIKTIMOLOGI MODEL PENGATURAN PERLINDUNGAN HUKUM PIDANA BULLYING DI LINGKUNGAN SEKOLAH - Novita Erdatimulia; Rachma Sofi Lestari; Noerma Kurnia Fajarwati (Gapenas Publisher, 2022)
Bullying is one of the most common cases in children, especially in the school environment. The purpose of this study is to analyze the model of legal protection for children who are victims of bullying in schools according to the victimization approach. The research method uses a normative juridical approach which is analyzed qualitatively by reviewing the legal protection of victims of bullying based on Law Number 35 of 2014 concerning Child Protection. The results of this study conclude that legal protection for children who are victims of bullying in the school environment can be carried out with the procedural rights model and the services model. The procedural rights model for children emphasizes the importance of the victim's activity in the criminal justice process to assist the public prosecutor in the case examination process. While in the service model, children who are victims of bullying at school are also entitled to compensation for the bullying, both physical and psychological, because the psychological impact experienced by victims can trigger feelings of trauma in children so that children who become victims of bullying tend to isolate themselves from their environment, even to depression and suicide